Uji Antioksidan Ekstrak Etanol Buah dan Biji Mengkudu (Morinda citrifolia L.) dengan Metode DPPH (1,1-diphenyl-2-picrylhydrazyl) - Pranita Aritrina; Parawansah Parawansah; Nurul Ardani (Halu Oleo University, 2017)
ABSTRACT Background: Free radicals and antioxidant were widely discussed in world of health because most of the diseases were initiated by presence of oxidation reaction in the body. The process of free radical formation could be inhibited by the presence of antioxidant. Antioxidant was a compound that can protect the biological system in the body. Research Purpose: This research aimed to analyze the potential of fruits and seeds of Morinda citrifolia L. as antioxidant which could counteract free radicals using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Research Method:This research used experimental method with post test only control design. The research was located in Integrated Laboratory of Faculty of Medicine and Pharmacy Laboratory of Faculty of Pharmacy of Halu Oleo University. Samples of this research were fruit and seed ethanol extract of Morinda citrifolia L.which were taken in West Kendari, Kendari City. The independent variables from this research were fruit ethanol extract and seed ethanol extract of cheese fruit and dependent variable was antioxidant potential. Potential and antioxidant activity (IC50) were tested by measuring DPPH (1,1-diphenyl-2-picrylhydrazyl) uptake using a spectrophotometer. Antioxidant activity (IC50) was analyzed using a linear regression equation. Research Result:The result of this research showed that there was a color changing of DPPH from purple to yellow on fruits ethanol extract and seeds ethanol extract of Morinda citrifolia L. and had antioxidant activity about IC50 398,99 ppm and 401,37 ppm, respectively.Conclusion: Conclusion from this research revealed that fruit ethanol extract and seed ethanol extract of Morinda citrifolia L.has weak antioxidant activity.Keywords : Antioxidant activity, DPPH method, IC50, Morinda citrifolia L.